Micro-entrepreneurship in Niger: factors affecting the success of women street food vendors - Otoo, M.; Ibro, G.; Fulton, J.; Lowenberg-Deboer, J. (Informa UK Limited, 2012)
Micro-entrepreneurship in the informal sector plays a vital role in generating employment and income in West Africa. In this article, the authors examine business success factors for micro-entrepreneurs involved in the production and sale of street foods in Niger, drawing on the resource-based view theory. Business success was measured by size of firm and vendor's perception of enterprise growth. Their results indicate that business experience is an important success factor, while the need for cash is a constraint for business success. A rare resource, limited access to financial assets translates into limited opportunities for growth of these informal micro-enterprises into viable businesses.